Pengaruh Risiko Pembiayaan Dan Risiko Operasional Terhadap Kinerja Keuangan Pada PT Bank Tabungan Pensiunan Nasional (BTPN) Tbk Periode 2014-2023 - Devia Nur Ayuni; Jamaluddin (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The aim of this research is to determine the influence of Financing Risk and Operational Risk on Financial Performance at PT Bank Tabungan Pensiunan Nasional (BTPN) Tbk. The variables used in this research are Financing Risk and Operational Risk, while the dependent variable used is Financial Performance. The method used is a quantitative method. The population in this research is in the form of financial position reports and profit and loss statements for the 10 year period 2014-2023. The analytical method used in this research is multiple linear regression analysis. Data analysis used SPSS version 26 software. Data analysis used descriptive statistics, classic assumption tests, simple and multiple linear regression analysis, coefficient of determination analysis and hypothesis testing. The results of this research show that Non-Performing Loans have a negative effect on Return On Assets with the hypothesis test obtained by the value Tcount < Ttable or (-2.778 < 2.306). This is also confirmed by the significant value (0.027 < 0.05). Meanwhile, Operational Costs Operational Income has a negative effect on Return On Assets. By hypothesis testing, the value Tcount < Ttable or (-3.056 < 2.306) or (0.018 < 0.05) is obtained. Non-Performing Loans and Operational Costs Operational Income shows that there is a significant influence simultaneously on Return On Assets with the Hypothesis Test which obtained a value of Fcount > Ftable or (8.529 > 4.74), this is also reinforced by a significant value of <0.05 or (0.013 < 0.05 ).